Implementing media literacy in the classroom - Biljana Temelkova; Julijana Zlatevska; Saska Delova (Institute of Communication Studies, 2022)
Social networks use a variety of models from the spectrum of web technologies. These tools were designed for entertainment and communication purposes, and the most commonly used among students are the social media tools. Knowing this, teachers have incorporated traditional teaching strategies as part of increasing the ability of students to grasp the objectives. Considering that most students find social media tools interesting, most researchers have supported this strategy as one of the most innovative methods of improving the learning outcomes. Students today can learn almost everything on their own or with their teachers using the Internet, talk to people from all over the world, share experiences with their peers, get acquainted with the world and other people, customs and cultures through their own personal experience. Researching a particular topic to find information, literature by authors from around the world and literary criticism, there are things that can open their view of the world, as well as enable them to think critically and creatively. These are some of the most significant benefits of a global network. This study wants to indicate the level of awareness in teachers and students about the proper use of social media and media literacy as well as to address the necessity to overcome the lack of media literacy knowledge within youth as well as the wider population. It also focuses on pointing out the dangers that social media causes with illiterate youth. Students who daily take in a huge amount of information from a wide array of sources, are going to become better critical thinkers and smart consumers that recognize the point of view and recognize the author's goal. Hopefully in future, teachers will pay more attention to what extent and in what manner their students use social media and pay particular attention to teach them how to be more alert when using social media.